Intentions and behaviours of using digital technology for health-related purposes by older adults: insights from the Time-to-Engage project. - Bobrowicz-Campos, E.; Camilo, C.; Pegado, E.; Pinheiro, G. G. (6º Congresso da Ordem dos Psicólogos Portugueses / XIII Congresso Ibero-americano de Psicologia, 2024)
The adoption of digital technologies in healthcare is expected to bring benefits at the individual and organizational levels. However, given the persistence of significant gaps related to access to and use of these technologies, the potential benefits may not reach everyone equally. Among the citizens who face the greatest difficulties in embracing and proactively using digital technologies, those of advanced age stand out. Since these citizens have a great demand for healthcare, which is due to age-related changes that impact on different areas of functioning, the generalised and rapid transition of health services to digital formats may put them at risk of having unequal access to necessary and quality healthcare. To prevent this scenario from becoming reality, it is mandatory to identify facilitators and barriers to access and use of digital technologies by citizens in question and define evidence-based solutions that guarantee equity in reaching digital transformation-related benefits. That’s how Time-to-Engage project came about. Time-to-Engage project is implemented by Iscte-IUL researchers, with financial support from La Caixa and FCT. Through a bottom-up approach, it intends to explore person- and context-related factors that interfere with the motivation of older adults to use digital technologies in health, and based on this, propose an explanatory model to inform elaboration of interventions that foster the adoption of these technologies, improving equity in access and use of health-related services, information, and products. Within this communication, we will present the preliminary results of the project and discuss their implications for health promotion and educational practices.